Respon Taiwan pada Kebijakan Pengurangan Ekspor Material Kritis oleh Tiongkok Tahun 2023-2025 - Lois Sintikhe Br Siahaan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Semiconductors are the backbone of the digital economy, and Taiwan plays a crucial role by controlling more than 60% of global semiconductor production and over 90% of advanced chip manufacturing. However, Taiwan’s semiconductor industry remains highly dependent on critical materials, most of which are supplied by China. From 2023 to 2025, China implemented policies aimed at reducing exports of critical materials, creating potential challenges for Taiwan’s semiconductor sector. This study aims to describe Taiwan’s response to these policies. The research uses a descriptive qualitative method with literature study techniques, utilizing secondary data from journals, books, official reports, and news sources. The analysis applies the Balance of Threat theory to explain Taiwan’s perception of China’s policies as a threat and the concept of balancing to examine Taiwan’s responses. The findings reveal two main strategies: strengthening national capabilities through risk identification, supply chain diversification, and rare earth recycling research, and enhancing cooperation with the United States to protect semiconductor industry security. These strategies reflect Taiwan’s balancing efforts to reduce dependence on China and maintain the resilience and security of its semiconductor industry.